Pengaruh CdCl2 terhadap Produksi Eksopolisakarida dan Daya Hidup Azotobacter - Hindersah, Reginawanti; Arief, Dedeh Hudaya; Soemitro, Soetijoso; Gunarto, Lukman (Jurnal Natur Indonesia, 2009)
The contamination of toxic heavy metal Cadmium (Cd) in soils will be endanger the human health because it ismore available comparing to another toxic heavy metals. One method of Cd-contaminated soil bioremediation isusing exopolysachharide-producing bacteria Azotobacter. Exopolysachharides (EPS) can mobilize Cd through theformation of complex Cd-EPS which sequentially can increase the availability of Cd for plants uptake. A laboratoryexperiment has been done to study the EPS production and the viability of six Azotobacter isolates in the liquidculture containing 0.01, 0.1, and 1 mM CdCl2. The bacteria were cultured in liquid medium with and without CdCl2 for72 hours at room temperature. The EPS production was determined by gravimetric method after precipitationusing acetone and centrifugation at 7000 rpm. The result was that all of Azotobacter isolates produce EPS in thepresence of CdCl2. In the culture with 1 mM CdCl2, the density of Azotobacter sp. isolate BS3, LK5, LKM6 increasedsignificantly, and that of isolate LH16 decreased. No significant effect of CdCl2 on the density of isolate BS2 andLH15. This research suggested that some Azotobacter isolates were relatively resistence to the Cd and could bedeveloped as biological agents in Cd-contaminated soil bioremediation.